Surface magnetism of non-ideal iron borate single crystal - Maksimova, E.M.; Nauhatsky, I.A.; Strugatsky, M.B. (Functional Materials, 2008)
Considered is the influence of crystalline structure imperfections in near-surface layer of easy-plane weak ferromagnet iron borate, FeB0₃, on the effects of surface magnetism observed therein. It is shown that the surface reconstruction and point defects therein change the surface magnetic properties of the crystal very considerably. Розглянуто вплив недосконалості кристалічної структури приповерхневого шару легкоплощинного слабкого феромагнетика борату заліза FeB0₃ на ефекти поверхневого магнетизму, що спостерігається у ньому. Показано, що реконструкція поверхні і наявність в ній точкових дефектів значно змінюють поверхневі магнітні властивості цього кристала. Рассмотрено влияние несовершенств кристаллической структуры приповерхностного слоя легкоплоскостного слабого ферромагнетика бората железа, FeB0₃, на эффекты наблюдаемого в нем поверхностного магнетизма. Показано, что реконструкция поверхности и наличие в ней точечных дефектов весьма значительно изменяют поверхностные магнитные свойства этого кристалла.